Vector borne disease control interventions in agricultural and irrigation areas in sub-Saharan Africa: A systematic review. - Levi Kalitsilo; Leila Abdullahi; Nyanyiwe Mbeye; Lily Mwandira; Hleziwe Hara; Collins Mitambo; Rose Oronje (PLoS ONE)
Irrigation farming has raised concerns about the steady transmission and introduction of new vector-borne infectious diseases (VBD) in the areas involved. This systematic review aimed to determine interventions that are effective for the management and control of VBDs in irrigation areas in sub-Saharan Africa (SSA). We searched the literature on VBD interventions in SSA from published and grey literature without specifying the publication year. A search strategy identified 7768 records from various databases, and after screening, 16 were included in the final analysis. Results showed various VBD control interventions were effective, including indoor residue spray (IRS), insect-treated nets (ITN), larva source management (LSM), mass drug administration (MDA), integrated vector management (IVM), and mollusciciding. IVM was commonly practiced, and its success was because of the complementarity of the various interventions involved. Successful VBD control interventions led to improved health amongst irrigation communities and consequently improved agricultural productivity. However, some challenges to these interventions were identified, which include seasonal changes and climate variability, insecticide and drug resistance, and farmers' attitudes toward accepting the interventions. Regardless, results showed that VBD control and management can be integrated into irrigation farming before or after the establishment of the irrigation scheme.